2010
DOI: 10.3109/1354750x.2010.522731
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-syntrophin protein is differentially expressed in human cancers

Abstract: We studied the expression of α1-syntrophin (SNTA1) protein in histologically confirmed esophageal, stomach, lung, colon, rectal and breast cancerous tissue samples. Our results suggest a significant decrease in the expression level of SNTA1 protein in both esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) compared with their respective controls while a significant increase in expression of SNTA1 protein compared with the normal tissue was observed in breast carcinoma samples. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In another such study, SNTA1 was found to be a potential marker of metastases or tumour progression, which could potentially aid in the classification of pre-malignant lesions, in tongue squamous cell carcinomas (SCCs) (Carinci et al , 2005). In addition, in our previous work, we observed an increase in SNTA1 protein levels in human breast carcinoma tissue samples when compared with their respective adjacent controls, suggesting that it has a role in the development and progression of carcinogenesis (Bhat et al , 2010). …”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In another such study, SNTA1 was found to be a potential marker of metastases or tumour progression, which could potentially aid in the classification of pre-malignant lesions, in tongue squamous cell carcinomas (SCCs) (Carinci et al , 2005). In addition, in our previous work, we observed an increase in SNTA1 protein levels in human breast carcinoma tissue samples when compared with their respective adjacent controls, suggesting that it has a role in the development and progression of carcinogenesis (Bhat et al , 2010). …”
mentioning
confidence: 64%
“…SNTA1, P66shc, and Grb2 have been shown to be upregulated in breast carcinomas and have roles in breast cancer development and/or progression (Jackson et al , 2000; Bhat et al , 2010). These proteins have also been implicated in the Rac1 protein activation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Genes, which were significantly associated with the pathway networks in IPA were searched in the literature for their roles in breast cancer and are compiled along with relevant references in Table  5 for upregulated genes and in Table  6 for downregulated genes. A total of 27 upregulated (ACHE [11], HSPA1L [12], NES [13], P2RY2 [14], PLCG1 [15], PPARGC1A [16], PRKCQ [17], SNTA1 [18], ALDOA [19], GNAO1 [20], SLC16A3 [21], TPI1 [22], ELL2 [23], CCNG1 [24], E2F6 [25], ESRRG [26], MAPK12 [27], HSD17B7 [28], TACC2 [29], DDX1 [30], MYH1 [31], UCP1 [32], PACSIN3 [33], PGM1 [34], TLN2 [35], ADIPOR1 [36], PITX1 [37]) and 8 downregulated genes (CELSR2 [38], PRKCB [39], KIT [40], MAP2 [41], TDGF1 [42], ELF1 [43], RUNX1 [44], TYMS [45]) showed association with breast cancer. Furthermore, the data files with the complete list of the upregulated and downregulated networks are presented in Additional files 3 and 4, respectively, for further reference.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study we have reported a dramatic up-regulation of the MKK6 in esophageal, stomach and colon cancers [7], and as already mentioned an upregulation has also been reported in prostatic carcinomas [5]. The expression pattern of MKK6 has never been systematically evaluated in breast cancer and the specific role of MKK6 in breast cancer progression is incompletely understood.…”
mentioning
confidence: 89%
“…In order to significantly augment our understanding of the metastatic process and to identify the specific targets for cancer therapy we need to single out the proteins and signaling pathways necessary for regulation of metastasis. In various cancers many proteins show differential expression and regulation [5][6][7]. One such protein is mitogen-activated protein kinase 6 (which from now onwards will be referred to as MKK6).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%